1998
DOI: 10.2169/internalmedicine.37.500
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Excretion of Pancreatic Stone Protein in Diabetic Nephropathy.

Abstract: Urinary pancreatic stone protein (PSP) levels were measured in 68 diabetic patients and 170 healthy controls to investigate the relationship between the progression of diabetic nephropathy and PSP excretion. Urinary albumin, N-acetyl-p-glucosaminidase (NAG), ax-microglobulin, creatinine clearance, and the blood PSP level were also determined in the diabetic patients. The urinary glucose level and glycemic control did not influence the urinary PSP level. In patients with normoalbuminuria (urinary albumin <20 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 13 publications
2
8
0
Order By: Relevance
“…Another interesting observation in this study was that PSP/REG Iα associated with eGFR and SCr. Previous studies reported that urinary PSP/REG Iα excretion is increased in patients with renal disease and diabetic nephropathy [14,21]. This study revealed that serum PSP/REG Iα levels were associated with eGFR in patients with and without T2DM.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Another interesting observation in this study was that PSP/REG Iα associated with eGFR and SCr. Previous studies reported that urinary PSP/REG Iα excretion is increased in patients with renal disease and diabetic nephropathy [14,21]. This study revealed that serum PSP/REG Iα levels were associated with eGFR in patients with and without T2DM.…”
Section: Discussionsupporting
confidence: 61%
“…It has been found in the urine and renal calculi of healthy individuals [13], which suggested a physiological role of PSP/REG Iα in the kidney. Sobajima et al reported that urinary PSP/REG Iα was increased significantly in patients with various renal diseases, including diabetic nephropathy [14,15]. Moreover, a previous study by the present researchers has found increased serum levels of PSP/REG Iα in patients with diabetic nephropathy [16].…”
Section: Introductionsupporting
confidence: 62%
“…1 ). Furthermore, it has been also identified in human kidney and urine which is increased in diabetic patients [21] , [22] , suggesting that Reg1 may be involved in diabetic kidney hypertrophy as a kidney growth factor. As EGF in the fluid of collecting duct cysts has been shown to stimulate the cyst growth, a similar role of Reg1 in proximal tubule cysts will be anticipated [1] .…”
Section: Discussionmentioning
confidence: 97%
“…Sobajima et al reported that urinary PSP excretion was increased from the initial stage of diabetic nephropathy and the increase became more marked as nephropathy progressed. They suggested that increased PSP excretion might reflect renal tubular dysfunction (79). Total serum PSP level tends to increase in severe acute pancreatitis than in mild acute pancreatitis (76,80).…”
Section: Anti-inflammatory Activity and Prognostic Indicatormentioning
confidence: 99%